SINTESSI N-LAUROIL SERINAMIDA MELALUI REAKSI AMIDASI SERIN DENGAN METIL LAURAT DAN REAKSI AMIDASI SERIN DENGAN LAUROIL KLORIDA - Friskila Delfia Nande (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2020)
Research on synthesis N-lauroyl serinamide through serine reaction with methyl laurate and lauroyl chloride has been carried out. Synthesis N-lauroyl serinamide by two reaction methods, the first method was through the esterification reaction of lauric acid to produce methyl laurate and then an amidation reaction was carried out by serine to produce N-lauroyl serinamide with percent yield of 73.86% and HLB value of 6.54. Through the FTIR test showed vibration absorption of the carbonyl amide group at wave number 1624.96 cm-1. The second method is through the chlorination reaction where lauric acid is converted to lauroyl chloride and then an amidation reaction is carried out by serine to produce N-lauroyl serinamide with percent yield of 93.75% and HLB value of 7.27. Through the FTIR test showed vibration absorption of the amide carbonyl group at wave number 1631.78 cm-1. The result shows that N-lauroyl serinamide can be synthesized through serine reaction with methyl laurate and lauroyl chloride which can be used as an emulsifier o/w (oil in water).